2016
DOI: 10.3233/bsi-160133
|View full text |Cite
|
Sign up to set email alerts
|

Building up spectral libraries for mapping erythrocytes by hyperspectral dark field microscopy

Abstract: Abstract. BACKGROUND:Red blood cells (RBC) are obtained by non-invasive methods and widely used for diagnostic tests of health status. Hyperspectral Dark Field Microscopy (HDFM) is a promising technique for nanoscale bio imaging and spectral analysis without additional sample preparation. OBJECTIVE: Develop a protocol for human RBC characterization by HDFM, checking the feasibility of a reference spectral library that can image and afford a new comprehensive descriptor of RBC status. METHOD: A step-by-step pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…3 the HDFM spectra registered for phospholipids and protoporphyrin IX, which are important components of the RBC membrane and sub-membrane regions, are shown. The acquisition of these spectra was carried out as previously reported 18 (see also details in the Supplementary Information). In Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 the HDFM spectra registered for phospholipids and protoporphyrin IX, which are important components of the RBC membrane and sub-membrane regions, are shown. The acquisition of these spectra was carried out as previously reported 18 (see also details in the Supplementary Information). In Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using spectral classification map and their percentage distribution, created by the spectral mapping software, the HDFM spectral features are precisely described, therefore changes occurring in the samples are reflected in changes of HDFM spectral distribution 15 , 16 . We focused on HDFM for the comprehensive and advanced imaging of complex biological scenarios such as human red blood cell (RBC) membrane 17 , and first published the healthy adult RBC imaging by a library of 8 spectral end-members with their typical distribution map 18 . In the RBC membrane and sub-membrane regions, cytoskeleton proteins, phospholipids and membrane-bound hemoglobin are the main constituents.…”
Section: Introductionmentioning
confidence: 99%
“…CellSave (Veridex, USA) and Streck (Streck, USA) tubes have been used to stabilize tumor cells in blood but analytical reports have shown that they lead to the loss of 40 to 60% of tumor cells spiked in blood [98]. In fact, blood cell membranes remain intact for up to 5 hours [99] after blood collection and degrade rapidly and dramatically after that (Dr Carla Ferreri, personal communication). For this reason, the ISET ® system manufacturer’s guidelines indicate that blood has to be treated by the ISET ® System within 5 hours after blood collection.…”
Section: Discussionmentioning
confidence: 99%
“…Mean values obtained for unselected RBCs and mature RBCs are summarized in Table 1 and reported as percent intervals of the fatty acid families. Further research is ongoing on mature RBC membranes and lipidome characterization, also using innovative biophotonic methodologies, recently discovered in our laboratories [47]. …”
Section: Fatty Acid Cohort To Examine Membrane Balance and Human Pmentioning
confidence: 99%